Application of bentonite for the construction of process wells for bore-hole mining of uranium - A. G. Ivanov; S. A. Alexandrov; I. A. Kurashov; D. A. Ivanov; P. E. Shikhov; Iu. A. Arsentev; A. P. Nazarov; O. Iu. Glotova (Известия высших учебных заведений: Геология и разведка, 2020)
Production of uranium by the method of bore-hole mining (BHM) is carried out from productive water-bearing formations represented by sands of various sizes. The beds are opened by the process well drilling using bentonite clay mud. This is accompanied by colmatation of the near-filter zone (NFZ) rocks. The performed studies showed the need for the complete removal of clay mud from the NFZ at the stage of well construction. It is shown that this can be done by the methods of interval-by-interval filter development or by the collapse of the productive horizon sands when NFZ after-filter washing with technical water. Laboratory tests on the chemical resistance of bentonite sleeves to the acid solutions action were carried out. Geological and process conditions for the use of bentonite sleeves for waterproofing the bore-hole annulus of process BHM wells were defined.